Fabrication of Porous Hydroxyapatite Granules as an Effective Adsorbent for the Removal of Aqueous Pb(II) Ions - Duyen Thi Le; Thao Phuong Thi Le; Hai Thi Do; Hanh Thi Vo; Nam Thi Pham; Thom Thi Nguyen; Hong Thi Cao; Phuong Thu Nguyen; Thanh Mai Thi Dinh; Hai Viet Le; Dai Lam Tran (Journal of Chemistry)
Porous hydroxyapatite (HAp) granules have been successfully fabricated from a HAp powder precursor and polyvinyl alcohol (PVA) additive by a simple sintering process. The composition and microstructures of the HAp were characterized by X-ray diffraction (XRD) and scanning electron microscope (SEM) equipped with an energy dispersive X-ray (EDX) spectrometer. The effects of sintering temperature and PVA/HAp mass ratios on color, water stability, morphology, and chemical composition of HAp are discussed. Optimum conditions for the fabrication of HAp granules were found to be a PVA/HAp mass ratio of 3/20 and a sintering temperature of 600°C for 4 h. Accordingly, the obtained HAp is white in color, is in the granular form with a size of about 2 × 10 mm, and has a specific surface area of 70.6 m2/g. The adsorption of Pb2+ onto the as-prepared HAp granules was carried out in aqueous solution by varying the pH, the adsorbent dose, the initial concentration of Pb2+, and the contact time. The results of adsorption stoichiometry of Pb2+ on the HAp granule adsorbent were fitted to the Langmuir adsorption isotherm model (R2 = 0.99). The adsorption capacity and removal efficiency of the HAp granule adsorbent for Pb2+ under optimal conditions were found to be 7.99 mg/g and 95.92%, respectively. The adsorption process obeyed a pseudo-second-order kinetic model with R2∼1. The porous HAp granules studied in this work showed potential for the removal of Pb2+ from industrial wastewater.